2007
DOI: 10.1038/labinvest.3700667
|View full text |Cite
|
Sign up to set email alerts
|

Matrix Gla protein is involved in elastic fiber calcification in the dermis of pseudoxanthoma elasticum patients

Abstract: Mature MGP (Matrix g-carboxyglutamic acid protein) is known to inhibit soft connective tissues calcification. We investigated its possible involvement in pseudoxanthoma elasticum (PXE), a genetic disorder whose clinical manifestations are due to mineralization of elastic fibers. PXE patients have lower serum concentration of total MGP compared to controls (Po0.001). Antibodies specific for the noncarboxylated (Glu-MGP) and for the g-carboxylated (Gla-MGP) forms of MGP were assayed on ultrathin sections of derm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
82
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(92 citation statements)
references
References 42 publications
10
82
0
Order By: Relevance
“…The immunoreaction for ucMGP, the inactive form of MGP, was slightly more intense on PXE elastic fibers compared with controls (Tables 3 and 4). Moreover, as already reported, 20 it was confirmed that ucMGP antibodies were associated with either bulky and finely dispersed mineral precipitates inside elastic fibers (Figure 5c), whereas cMGP antibodies nicely and precisely localized at the border of the mineralized areas of calcified elastic fibers (Figure 5d). …”
Section: Electron Microscopysupporting
confidence: 64%
See 2 more Smart Citations
“…The immunoreaction for ucMGP, the inactive form of MGP, was slightly more intense on PXE elastic fibers compared with controls (Tables 3 and 4). Moreover, as already reported, 20 it was confirmed that ucMGP antibodies were associated with either bulky and finely dispersed mineral precipitates inside elastic fibers (Figure 5c), whereas cMGP antibodies nicely and precisely localized at the border of the mineralized areas of calcified elastic fibers (Figure 5d). …”
Section: Electron Microscopysupporting
confidence: 64%
“…In general, PXE fibroblasts were less positive for cMGP compared with controls (Table 3). 20 In the extracellular space, the distribution of positive immunostaining for cMGP and ucMGP gave results almost identical to those in patients with the PXE-like syndrome (Figure 5c and d). Irrespective of the calcification degree, elastic fibers were the only extracellular matrix component positive for both antibodies.…”
Section: Electron Microscopysupporting
confidence: 53%
See 1 more Smart Citation
“…12,13 Indeed, several studies reported alterations in systemic blood components in PXE patients and mouse models due to MRP6 deficiency. [14][15][16][17][18][19][20] Accordingly, PXE was assumed to be primarily a metabolic disorder. 12,[21][22][23] In contrast, results of several studies also point to a local role for ABCC6/MRP6 as expression of the protein was detected in dermal fibroblasts from healthy controls whereas it was found to be absent in fibroblasts from PXE patients.…”
mentioning
confidence: 99%
“…Importantly, cMGP is not detected in lesional skin from PXE patients, which supports its possible implication in the abnormal mineralization process seen in the disease (see Fig. 1) [20,21].…”
Section: Ggxc a Link Between Vitamin K-dependent Pathway And Mineralmentioning
confidence: 59%